Big Data Dalam Layanan Statistik Indonesia: Penerapan, Tantangan, dan Arah Masa Depan - Hadisha Shafa Anasya (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Industrial Revolution 4.0 has accelerated the development of technology and information. The availability of data and information is currently undergoing major changes. One of the technologies that will support the development of this revolution is big data technology. Therefore, BPS must be able to adapt to the use of big data in generating data. The purpose of writing this article is to explain the role of big data in improving the quality and effectiveness of statistical services in Indonesia. Through a literature review regarding the application of big data in BPS Indonesia, it has been carried out through various statistical publications, such as calculating the number of foreign tourists, analyzing the impact of COVID-19, and various studies in the economic and social fields. However, there are challenges ahead, such as access to operated big data and regulations that do not fully support it. To overcome the obstacles facing us, BPS will build basic principles, methodological standards, big data management infrastructure, collaborate with various parties, and increase the capacity of human resources (HR) for the development of big data and artificial intelligence. However, even though the application of big data still has challenges that must be faced, BPS is committed to continuing to overcome challenges and utilize the potential of big data to improve accountability and the quality of official statistics in the future.